2004
DOI: 10.1124/jpet.104.070094
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic Blockade Affects Initial Drug Distribution Due to Decreased Cardiac Output and Altered Blood Flow Distribution

Abstract: ␤-Adrenergic receptor blockers decrease intravenous anesthetic dose requirements. The present study determined the effect of propranolol on indocyanine green and antipyrine disposition from the moment of rapid intravenous injection. Antipyrine is a physiological marker that distributes to a volume as large as total body water in a blood flow-dependent manner and is a pharmacokinetic surrogate for many lipophilic drugs, including intravenous anesthetics. Antipyrine and indocyanine green disposition were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 37 publications
0
21
0
2
Order By: Relevance
“…29 β-Blockers may affect the pharmacokinetics of sevoflurane and fentanyl via a decrease in cardiac output and changes in the distribution of organ blood flow. 30 The blood pressure and heart rate of patients in the present study were not affected by esmolol infusion, indicating no effect on cardiac output, so any changes in the pharmacokinetics of sevoflurane and fentanyl are unlikely to have been significant. This finding is supported by a previous study in which it was stated that esmolol infusion had no effect on the metabolism of drugs with a large hepatic extraction ratio.…”
Section: Sparing Effect Of Esmolol On Sevofluranementioning
confidence: 83%
“…29 β-Blockers may affect the pharmacokinetics of sevoflurane and fentanyl via a decrease in cardiac output and changes in the distribution of organ blood flow. 30 The blood pressure and heart rate of patients in the present study were not affected by esmolol infusion, indicating no effect on cardiac output, so any changes in the pharmacokinetics of sevoflurane and fentanyl are unlikely to have been significant. This finding is supported by a previous study in which it was stated that esmolol infusion had no effect on the metabolism of drugs with a large hepatic extraction ratio.…”
Section: Sparing Effect Of Esmolol On Sevofluranementioning
confidence: 83%
“…Arterial drug concentrations versus time data collected before recirculation were fit to the sum of two Erlang distributions in our earlier studies in dogs (e.g., Krejcie et al, 1996aKrejcie et al, ,b, 1997Avram et al, 1997Avram et al, , 2000 and humans (Avram et al, 2004). The choice of the dual central circulation pathway model over a single pathway model in those studies was based on both subjective and statistical assessments (Krejcie et al, 1996b).…”
Section: Discussionmentioning
confidence: 99%
“…[22] Inhibitory G protein coupled receptor agonists act on postsynaptic inhibition via G protein coupled potassium channels or via the presynaptic inhibition of neurotransmitter release. [22] Avram et al [23] demonstrated that beta adrenergic receptor antagonists decreases hepatic blood flow, metabolism of opioids and reduces the need for postoperative use of analgesics.…”
Section: Discussionmentioning
confidence: 99%